Existence of Legal Certainty for Foreign Investors in Danantara as a Form of Investment Governance Reform - Widiatno, Hector Stanley; Harris, Freddy (Fakultas Hukum Universitas Islam Jakarta, 2025)
Legal certainty for foreign investors is a crucial factor in supporting the stability and competitiveness of national investment. The establishment of the Investment Management Agency Daya Anagata Nusantara (Danantara) as Indonesia’s sovereign wealth fund marks a significant reform in national investment governance. This study aims to analyze the existence of legal certainty for foreign investors through Danantara as a manifestation of investment governance reform, using a normative juridical method with statutory and conceptual-analytical approaches. The results show that Danantara possesses legal capacity as a state investment manager capable of accommodating various foreign investment schemes such as foreign direct investment, co-investment funds, and public–private partnerships. Legal certainty is realized through the principles of regulatory clarity, freedom of contract, non-discrimination, and institutional independence. The application of the principle of equitable efficiency reflects a balance between legal certainty and social justice, consistent with the theories of Sudikno Mertokusumo and John Rawls. It is concluded that Danantara strengthens legal and justice certainty for foreign investors and serves as a strategic instrument for reforming national investment governance. It is recommended to enhance regulatory transparency and harmonization to ensure the effectiveness and sustainability of investment policies.